Radical-Transformative Agency: Continuities and Contrasts With Relational Agency and Implications for Education - Stetsenko, Anna (Frontiers in Education, 2019)
The recent scholarship on agency is mostly centered around a relational (also known as situative, contextual, distributed, and ecological) approach that draws attention to agency being situated in context and contingent on sociocultural interactivities and contextual dynamics. My central argument is that there is a residue of passivity in these conceptions. Illustrative of this are the works by Bietsa and colleagues which I analyse to reveal conceptual flaws that need to be addressed. To overcome these flaws, it is important to reconstrue no less than the very basic premises about human development, context/reality, and teaching-learning to foreground a more radical view of agency conducive to combatting inequalities and injustices in education. In the alternative approach, termed the Transformative Activist Stance, human development is posited to be not only fully immersed in the world and its contextual dynamics but, more critically, realized by each individual's agentive contributions to communal practices, whereby these practices are changed as a whole every time a person acts as an active member of community. The emphasis is on the nexus of people changing the world and being changed in this very process of them changing the world—as two poles of one and the same, bi-directional and recursive, co-constitution of people and the world in a simultaneous self- and world-realization. People never merely react or respond to what exists but agentively act in co-realizing both the world and themselves. Agency in this account is accorded with a formative role in the processes of co-realizing both human development, the overall sociohistorical dynamics, and the world itself. Importantly, agency development is contingent on access to cultural tools that need to be provided by society and agentively taken up by each individual. There are starkly contrasting sociopolitical conjectures and implications geared to the issues of inequalities and injustices in education. The notion of a radical-transformative agency is deployed in order to expose and overcome ideologies of passive adaptation to, and acquiescence with, the existing order of things and the world as it presumably “is.”